Securities Litigation and Stock Returns: an Event Study - Georgi Kalchev (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
This paper executes a simple event study of the effects of securities litigation on stock returns. Securities litigation is a common occurrence on the US investment markets, via which shareholders aim to recover losses they have suffered as a result of managerial misconduct. Filing lawsuits, however, signals to the market in general that there is something wrong with the company, unless the market knows it already. In that case, litigation may have negative consequences on future stock returns of the company. Applying t-tests, this paper tests this hypothesis and finds that significant negative stock reaction to litigation is present but not overwhelmingly. Positive reaction to lawsuits can sometimes be observed. Negative reaction, however, is twice as common as positive reaction to lawsuits. Shareholders should not be concerned that filing a securities lawsuit will necessarily result in stock return declines.
Conference: International Conference Managerial Solution for global & local markets during the crisis, Nessebar 9-12 September 2009
Keywords: 330; shareholder litigation; event study; pulse dummies